"Ruski oktober" v znanstvenem opusu zgodovinarja Marjana Britovška - Lešnik, Avgust (Prispevki za novejšo zgodovino, 2018)
Marjan Britovšek (1923-2008) was the first Slovenian historian to systematically and scientifically research the history of the international workers movement', especially Stalinism and destalinisation in the Soviet Union, while he was at the same time known as the foremost Slovenian/Yugoslav expert in the conflicts between the fractions in the former Soviet Union and Comintern. Britovšek's work on this topic culminated in the lengthy books, crowning the author's research of the "Russian reality" since the beginning of the 19th century until the destalinisation in the 1950s and 1960s: Revolucionarni idejni preobrat med prvo svetovno vojno (Revolutionary Ideological Watershed During World War I., 1969); Boj za Leninovo dediščino (The Struggle for Lenin's Legacy, 1976); Carizem, revolucija, stalinizem (Tsarism, Revolution, Stalinism. Social Development in Russia and the Pespectives of Socialism, 1980); Stalinov termidor (Stalin's Thermidor, 1984). With his books, based on the archive and documentary materials, he asserted himself as one of the renowned international researchers of Stalinism. Britovšek did not research the "Russian October" merely as the Bolshevik act of the revolutionary takeover of power (the envisioned Bolshevik Revolution), but rather - as it is obvious from the titles of the aforementioned books - understood and examined it in the wider framework of issues, topics, and time. This framework began with Russian Revolution 1905-1907 as a "dress rehearsal" for both revolutions that took place in 1917, and extended into the middle of the 1930s when Stalin with his "administrative revolution from above" ("Thermidor"), ultimately put an end to the ideals of the October Revolution.
Keywords: Britovšek, Marjan; delavsko gibanje; mednarodno delavsko gibanje; oktobrska revolucija 1917; zgodovinski pregledi